Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. PP Propertik Tbk : (Proyek Grand Kamala Lagoon Kota Bekasi) - Dhea Septia Rani; Hasanuddin (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to measure the influence of the work environment and work discipline on employee performance at PT. PP Properti Tbk (Grand Kamala Lagoon Project, Bekasi City). The population and sample amounted to 61 people or all employees at PT. PP Properti Tbk (Grand Kamala Lagoon Project, Bekasi City). The sampling technique used in this research used saturated samples. The data collection tool in this research used a questionnaire with 61 respondents. The design used in this research was SPSS 26 for windows. The results of this research show that: (1) Work Environment has a significant effect on Employee Performance, (2) Work Discipline does not have a significant effect on Employee Performance, (3) Work Environment and Work Discipline has a significant effect on Employee Performance at PT. PP Properti Tbk (Grand Kamala Lagoon Project, Bekasi City). This research provides suggestions to PT. PP Properti Tbk (Grand Kamala Lagoon Project, Bekasi City) to be able to pay more attention to environmental conditions, facilities, air conditioning as well as the delegation or occurrence of seniority among employees and pay attention to the conditions of work discipline experienced by its employees so that employee performance continues to increase.